Precision measurement of atom-dimer interaction in a uniform planar Bose gas - C. Maury; B. Bakkali-Hassani; G. Chauveau; F. Rabec; S. Nascimbene; J. Dalibard; J. Beugnon (Physical Review Research, 2023)
Cold quantum gases, when acted upon by electromagnetic fields, can give rise to samples where isolated atoms coexist with dimers or trimers, which raises the question of the interactions between these various constituents. Here we perform microwave photoassociation in a degenerate gas of ^{87}Rb atoms to create weakly bound dimers in their electronic ground level. We determine the complete energy diagram of one hyperfine manifold of the least-bound level, which we accurately reproduce with a simple model. Then, from the density-induced shift of the photoassociation line, we measure the atom-dimer scattering length for two weakly bound states of the molecular potential.